Authenticity Matters: The Reading Practices of Swedish Young Adults and Their Views of Public Libraries. Issue 1 (2nd July 2020) - Hedemark, Åse
ABSTRACT: Research speaks of a disconnect between young adults and library culture. Young adults, despite having overall low expectations, often show dissatisfaction with library services, while librarians perceive teens as both a prioritized user group, and a problematic group of users. Ninety-two young adults participated in a focus-group study. The interviews revolved around their views on reading and public library services. Results showed that young adults' choices to engage in reading practices are influenced by the context of the practice, the motivation for engaging in the practice and the format used.